Relationship Between the Role of Parents and the Influence of Peers on the Consumption of Alcohol in Young Men in Hamlet VII Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency - Supriati Supriati (Journal of Midwifery and Nursing, 2022)
Based on WHO data, western Europeans consume more alcohol, people who consume the least alcohol are found in the countries of Southern Asia. On the other hand, China, America and Russia based on their population are the countries that consume the most alcohol in the world. That sociologically the consumption of alcoholic beverages in Indonesia is motivated by the customs and habits of their community. Alcoholic Drinks are all types of drinks that contain ethanol which is also called grain alcohol. The purpose of the study was to determine the relationship between the role of parents and the influence of peers on consuming alcohol in adolescents in Hamlet VII, Sei Rattan Village, Percut Sei Tua District, Deli Serdang Regency in 2021. Types This research is an analytic descriptive which aims to describe the reality of the object being studied objectively about the relationship between the role of parents and the influence of peers on the consumption of alcohol in young men in Hamlet VII. This research was conducted from October 2021 - January 2022 with a population of 70 and a sample of the entire population, namely 70 respondents. The sampling technique used was total sampling with the research instrument, namely the questionnaire. Management of data editing, coding, tabulating, and data entry research results the majority of respondents consume alcohol 54 respondents (77.1%) and the minority does not consume alcohol 16 respondents (22.2%) the majority do not play a role 56 respondents (80%) the minority plays a role 14 respondents (14%) majority unaffected 17 Respondents (24.3%) minority affected 53 Respondents (53%), the results of the study of the relationship between parental roles and alcohol consumption were obtained (OR) = 229.667% CI = 22,056-2391,527 and P value 0.000 < 0.05, the relationship between peer influence on alcohol consumption was obtained (OR) = .008% CI = 001-055 and P value 0.000 < 0.05, It is expected that adolescents do not consume alcohol because consuming alcohol will cause poisoning in the brain and affect on the reproductive system.